The Role of Just-In-Time Implementation in Relation to Performance: An Exploratory Study - Isa, Che Ruhana; Keong, Tay Yew (Asian Journal of Accounting Perspectives, 2008)
This study investigates the relationship between the level of just-in-time (JIT) purchasing and manufacturing implementation and performance. The study employed a self-administered questionnaire survey to collect data from Malaysian manufacturing companies. The statistical tests provide empirical evidence that the level of JIT implementation is related to perceived performance. The findings reveal that the level of JIT adoption is positively related to both financial and non financial performance. In addition, the t-test results indicate that there are significant differences in the level of performance among the JIT firms and the non-JIT firms.